MINUPI uto Improve Disaster Mitigation Learning Outcomes pthere are Students with Disabilities - Siti Nurjannah (Pinisi Journal of Education and Management, 2022)
One of the lessons in disaster mitigation is awareness of disaster risk reduction using MINUPI media which provides real experiences of students with disabilities about natural disasters, especially erupting volcanoes. The purpose of the study is to improve learning outcomes and the activeness of students with special needs in disaster mitigation learning. The implementation of research in disaster mitigation learning follows the design of a type of classroom action research for 2 cycles, consisting of 4 activities, namely planning, action, observation and reflection. The application of disaster mitigation learning with MINUPI Media is carried out in several steps, starting with the planning stage where dividing students into groups, delivering learning objectives, presenting material, giving assignments to groups in the form of worksheets, practicing making MINUPI media and giving evalusai. The results showed that student learning outcomes improved in the time before applying learning with MiNuPi media compared to after media use. The learning results showed that the average class, which was originally 63.75 in the preliminary observation stage, increased to 68.12 in cycle I, and subsequently increased by 81.25 in cycle II. The classical completion, which was originally 25% at the preliminary observation stage, increased to 37.5% in cycle I, and to 100% in cycle II. Student activity increased from 25% at the preliminary observation stage, to 37.5% in cycle I, and to 100% in cycle II.